The Influence of Financial Attitude, Financial Knowledge and Income on Financial Management Behavior (A Study of MSMEs in Jombang Culinary Community) - Arrahima, Irea; Sucipto, Beni (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aims to analyze the influence of financial attitudes, financial knowledge, and income on the financial management behavior of MSMEs belonging to the Jombang Kuliner Community. This research is based on the phenomenon of low financial literacy among micro-entrepreneurs, which results in suboptimal financial management, despite the economic potential in the Jombang Kuliner area. This study used a mixed methods approach. Quantitative data were obtained through distributing questionnaires to 50 respondents using a Likert scale, while qualitative data were collected through in-depth interviews with several MSMEs to gain a more contextual understanding. The results of the partial T-test indicate that all three independent variables significantly influence financial management behavior. This means that the better the financial attitudes and knowledge possessed and the higher the income of entrepreneurs, the better their behavior in managing business finances. Qualitative findings support these results, where several MSMEs who have awareness of saving, making financial plans, and separating personal and business finances demonstrate more organized financial management. This study concludes that improving financial literacy and strengthening business income play an important role in shaping healthy and sustainable financial management behavior. The results of this study are expected to form the basis for developing more effective financial education programs for MSMEs, particularly in Jombang Regency